2012
DOI: 10.1186/1471-230x-12-42
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of omeprazole, famotidine, mosapride and teprenone in patients with upper gastrointestinal symptoms: an omeprazole-controlled randomized study (J-FOCUS)

Abstract: BackgroundIn Japan, treatment guidelines are lacking for patients with upper gastrointestinal symptoms. We aimed to compare the efficacy of different drugs for the treatment of uninvestigated upper gastrointestinal symptoms.MethodsThis was a randomized, open-label, parallel-group multicenter study. Helicobacter pylori-negative, endoscopically uninvestigated patients ≥ 20 years of age with upper gastrointestinal symptoms of at least moderate severity (Global Overall Symptom score [GOS] ≥ 4 on a 7-point Likert s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 29 publications
(54 reference statements)
1
26
0
2
Order By: Relevance
“…Follow up was from 4 to 52 weeks and there was a trend towards PPI being more eff ective than prokinetic therapy (RR=0.78; 0.60-1.02, P =0.06) ( Appendix 2 : Appendix Figure 9 ) but this did not achieve statistical significance. Two trials ( 57,62 ) showed PPI therapy was superior and one ( 66 ) reported no diff erence.…”
Section: Conditional Recommendation Very Low Quality Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Follow up was from 4 to 52 weeks and there was a trend towards PPI being more eff ective than prokinetic therapy (RR=0.78; 0.60-1.02, P =0.06) ( Appendix 2 : Appendix Figure 9 ) but this did not achieve statistical significance. Two trials ( 57,62 ) showed PPI therapy was superior and one ( 66 ) reported no diff erence.…”
Section: Conditional Recommendation Very Low Quality Evidencementioning
confidence: 99%
“…Th ere were no randomized studies comparing prokinetic therapy with placebo. Th ere were three trials ( 57,62,66 ) that compared PPI with prokinetic therapy in 680 dyspepsia patients. Follow up was from 4 to 52 weeks and there was a trend towards PPI being more eff ective than prokinetic therapy (RR=0.78; 0.60-1.02, P =0.06) ( Appendix 2 : Appendix Figure 9 ) but this did not achieve statistical significance.…”
Section: Conditional Recommendation Very Low Quality Evidencementioning
confidence: 99%
“…Hsu et al 8 reported that the efficacy of PPI was similar to prokinetics in patients with FD according to the Rome III criteria after 2 weeks of treatment. In another study of 23 The co-administration of PPI and prokinetics is commonly prescribed for patients with FD and is frequently recommended by clinical guidelines, although the efficacy has been questioned. The present study documented that combining DA-9701 with PPI provided no additional amelioration of dyspeptic symptoms compared with PPI or prokinetics alone.…”
Section: Discussionmentioning
confidence: 99%
“…The main treatments for these two symptoms are PPIs (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). If heartburn, acid regurgitation, and other symptoms that suggest gastroesophageal reflux disease had not been excluded from the dyspepsia symptoms, PPI treatment could have been more effective (24).…”
Section: Baysal Et Al Therapy For Uninvestigated Dyspeptic Patientsmentioning
confidence: 99%
“…The GOS score has been validated in patients with dyspepsia (12,13), and has previously been used in clinical studies of patients with dyspepsia to assess symptoms and treatment success (14)(15)(16)(17)(18)(19)(20). The GOS score measures the severity of the eight symptoms noted above using a 7-point Likert scale, which is defined as follows: 1=no complaint and no symptoms; 2=a minimal complaint that can be ignored easily and without effort; 3=a mild complaint that can be ignored with effort; 4=a moderate complaint that cannot be ignored, but does not influence daily activities; 5=a moderately severe complaint that cannot be ignored and occasionally limits daily activities; 6=a severe complaint that cannot be ignored and often limits concentration on daily activities; and 7=a very severe complaint that cannot be ignored, markedly limits daily activities, and often requires rest.…”
Section: Patientsmentioning
confidence: 99%